2012
DOI: 10.2478/s11756-012-0035-8
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical evaluation of proliferative activity (Ki-67 index) in different histological types of cutaneous basal cell carcinoma

Abstract: Evaluation of tumor cell proliferation status belongs to the basic prognostic indicators in a routine biopsy report. In cutaneous basal cell carcinoma (BCC), however, there are discrepancies about a true prognostic significance of this histopathological parameter. The aim of this study was to assess a proliferative activity (Ki-67 index) in BCCs of the skin. Biopsy specimens from 80 cutaneous BCCs (63 primary, 17 recurrent) of different histological types from 75 subjects (34 men, 41 women) were enrolled into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
(46 reference statements)
0
8
0
1
Order By: Relevance
“…In our study, the GEF-NPs group showed the lowest expression of ki-67, CD-31 and EGFR after treatment compared with the other three groups. A low degree of cell proliferation, MVD and EGFR generally correlates with slow tumor growth, higher degree of differentiation and hence more moderate clinical and biological behavior (Barto s et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the GEF-NPs group showed the lowest expression of ki-67, CD-31 and EGFR after treatment compared with the other three groups. A low degree of cell proliferation, MVD and EGFR generally correlates with slow tumor growth, higher degree of differentiation and hence more moderate clinical and biological behavior (Barto s et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…entretanto, a média de células em proliferação variou muito de um subtipo ao outro de cBc, apresentando baixa atividade proliferativa celular, apesar da variação. outro estudo 25 indica que um tumor individual não possui um padrão homogêneo de proliferação. o subtipo morfea apresentou a mais alta média de células em proliferação.…”
Section: Discussionunclassified
“…Immunohistochemical study was done to detect the Ki-67 nuclear antigen to evaluate the cellular proliferation and CD31 to detect the endothelial cells proliferation. Immunohistochemical comprised the following stages (20,21) :…”
Section: Immunohistochemical Stainingmentioning
confidence: 99%
“…The Ki-67 labeling index (LI) for cell proliferation was used five areas at high power (×400 magnification). A minimum of 500 cells were calculated, and the percentage among the number of cells that had a brown stained nucleus and the whole number of cells was calculated (20).…”
Section: Morphometric and Statistical Analysismentioning
confidence: 99%